DID MICROECONOMIC AND MACROECONOMIC FACTORS AFFECT STOCK PRICES? - Fenty Fauziah; Bun Yamin; Fitria Rahmah (Jurnal Ekonomi dan Manajemen, 2020)
This study to analyze and explain the factors that influence stock prices. The object of this research is the automotive and components sub sector manufacturing companies sector on the Indonesia stock exchange for periode 2010-2018. The variables used in this study are stock prices, micro economic factors and macro economic factors. Micro economic factors are projected by Debt to Equity Ratio (DER), Gross Profit Margin (GPM), Net Profit Margin (NPM), Price Earning Ratio (PER) and Return on Assets (ROA). Macro economic factors used as variables are inflation (INF), interest rates (INT) and Gross Domestic Product (GDP). Data analysis and hypothesis testing were carried out using the SmartPLS 3.0 program. The results of the study indicate that stock prices are determined by microeconomic factors projected by Net Profit Margin (NPM). Companies must keep trying to make a profit so that stock prices remain good, so investors are still interested in owning shares.